Virtual Pastor: Virtualization, AI, and Pastoral Care - Young, William (Theology and science, 2022)
This paper explores innovations in AI and virtual reality that could reshape pastoral care delivery. This includes approaches that preserve the paradigm of a human care provider interacting directly with a client, and others in which the provider is not present in real time or care is provided by a digital system. We investigate the feasibility of automated pastoral carebots and issues these would raise. We conclude that carebots are not yet able to provide pastoral care. However, technological progress ultimately may compel religious communities to confront new questions about the potential for automating relationships in ministry.